Regional Spread of Computer Technology in Hungary - Rechnitzer, János (Discussion Papers, 1990)
The paper analyses the relationships of electronization and the spatial socio-economic structure, more specifically, the spatial spread, appearance and presence of computers. The author’s aim is to present the spreading of the devices of computer technology, their spatial and temporal structure and space-forming functions of their forms of appearance. He demonstrates not only the economy and its supply, but also the possibilities of access to the devices as well as their spatial, settlement-network determinants. The author outlines the supply of the educational system with machines, its composition and changes, the regional characteristics of the degree of supply of the cultural, educational and extension training sphere with equipment. Finally, he attempts to show and outline the regional characteristics of the possible supply of the private sector, the population with computers by using indirect information.